Aplicação de metodologia QuEChERS para análise de alimentos - Donzelli Neto, João (2019)
Due to the problems associated with human and environmental contamination by chemical residues from farming, the development of efficient methods to analyze those residues is essential to control the abusive and excessive use. Therefore, this work shows a review about what is described in the literature on the applications of QuEChERS methodology, which is a fast, cheap, and environmental-friendly sample preparation technique, in the determination of chemical compounds in different matrixes. An introduction about the methodology is presented, highlighting the general of this procedure and its relevance in chemical analysis. Applications, focused on pesticides detection in food samples, are reviewed as well. Finally, future perspectives and trends of QuEChERS applications are briefly discussed.